The Effects of the COVID-19 Pandemic on the Digital Competence of Educators - García, Boni; Alario-Hoyos, Carlos; Pérez-Sanagustín, Mar; Morales, Miguel; Jerez, Oscar (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Covid-19 pandemic is having an undeniable impact on all the statements of society. Regarding teaching and learning activities, most educational institutions suspended in-person instruction and moved to remote learning during the lockdown of March and April 2020. Although nowadays many countries have progressively re-opened their educational systems, blended learning is a common practice aimed to reduce the spread of the Covid-19 disease. This disruption has supposed an unprecedented acceleration to the digitalization of teaching and learning. Teaching professionals have been forced to develop their digital competence in a short amount of time, getting mastery in the management of information, the creation of audiovisual contents, and the use of technology to keep their students connected. This Special Issue presents contributions regarding the adoption of distance learning strategies, experiences, or lessons learned in this domain.